Graphene with large flake diameter and high conductivity and preparation method thereof
Through the method of treating graphene by static expansion and peeling, the problems of structural failure and high energy consumption in the existing graphene preparation process are solved, and the preparation of large-size high-conductive graphene is realized, which has improved its application prospects.
Patent Information
- Application Number
- CN202510155206.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-21
- Publication Date
- 2025-03-25
AI Technical Summary
In the existing graphene preparation methods, redox method leads to damage to the graphene structure and affects the conductivity; the expanded graphite process produced in industrial production is complex, has high energy consumption, and has great environmental hazards, and has large water consumption in cleaning and uneven expansion, which damages the graphene structure.
A mixture of graphite, concentrated sulfuric acid and expansion agent is used for static expansion reaction, followed by adding a peeling additive for peeling treatment to obtain large-size highly conductive graphene. This method has no oxide intercalation, simple process, low energy consumption and environmental protection.
The preparation of large-size graphene has been achieved, with low structural damage, few defects, and significantly improved conductivity, which is suitable for a wide range of application prospects.
Smart Images

Figure CN119683610A_ABST
Abstract
Description
[0001] This invention patent application is a divisional application of a Chinese patent application with an application date of June 21, 2022, application number 202210705268.X, and invention name “A graphene with large sheet diameter and high conductivity and its preparation method”. Technical Field
[0002] The present invention relates to the technical field of graphene material preparation, and in particular to a graphene with a large sheet diameter and high conductivity and a preparation method thereof. Background Art
[0003] Graphene is a carbon atom with sp 2 A two-dimensional atomic crystal with a honeycomb hexagonal structure and a honeycomb lattice structure connected by hybridization. Among the current graphene preparation methods, the most widely used one is the redox method, or the expanded graphite exfoliation method, which is essentially a redox method in which the graphite is oxidized and then expanded and reduced before exfoliation. In the redox method, since graphite forms oxygen-containing functional groups in its structure during the oxidation process, they are removed during the reduction process and carbon atoms are also lost, which destroys the structure of the prepared graphene and affects its performance, especially its conductivity. Compared with the redox method, the graphene prepared by the graphite expansion and exfoliation method of the present invention has a more complete structure and must have better electrical conductivity, thermal conductivity and mechanical properties, etc. These excellent properties make graphene materials have a wider range of uses and application prospects.
[0004] Graphite is a typical layered mineral, with atoms in sp 2 The hybrid orbital forms a σ bond with three adjacent carbon atoms to form a hexagonal ring-shaped structural layer, which is bonded by van der Waals forces. z The orbital electrons interact with each other to form a delocalized large π bond. The π bond electrons are very active and can move freely within the layer, resulting in graphite having good electrical and thermal conductivity. At the same time, graphite has good chemical stability at room temperature and is not corroded by any strong acid, strong base or organic solvent, which makes graphite products chemically stable and resistant to corrosion. Due to the weak interlayer force and the chemical activity of π electrons, chemical substances can enter the graphite interlayer under certain conditions, so graphene can be prepared through the expansion-stripping process.
[0005] At present, although domestic and foreign scholars have conducted a lot of research work on graphene preparation and proposed various preparation methods, the following problems still exist: a large number of oxygen-containing functional groups are introduced in the process of producing graphene by the redox method, which destroys the graphene structure; industrially produced expanded graphite mostly adopts high-temperature expansion or microwave expansion, which has a complex process and high energy consumption, and has great environmental hazards; the washing process of expandable graphite consumes a lot of water, the expansion is uneven, and the exfoliation process destroys the graphene structure. Summary of the invention
[0006] The purpose of the present invention is to solve at least one of the above-mentioned deficiencies in the prior art. For example, one of the purposes of the present invention is to provide a method for preparing graphene with large sheet diameter and high conductivity, which has a simple preparation process, mild reaction, low energy consumption and environmental protection. For another example, another purpose of the present invention is to provide graphene with low structural damage, few defects, larger sheet diameter and excellent electrical properties.
[0007] In order to achieve the above object, the present invention provides a method for preparing graphene with large sheet diameter and high conductivity, the preparation method comprising the steps of:
[0008] Add graphite, concentrated sulfuric acid and an expander into a reaction container at a ratio of 1:3-12:10-30 g / ml / g, and stir and mix evenly to obtain a fluffy graphite mixture containing concentrated sulfuric acid and an expander;
[0009] statically expand the fluffy graphite mixture at a predetermined temperature for a predetermined time to obtain crude high expansion rate expanded graphite;
[0010] Adding a stripping aid to the crude high expansion rate expanded graphite to perform a stripping treatment to obtain a crude large-diameter graphene suspension;
[0011] Sedimenting and separating the crude large-sheet graphene suspension to obtain a refined large-sheet graphene dispersion;
[0012] The large-diameter purified graphene dispersion is filtered, washed, and dried to obtain large-diameter highly conductive graphene.
[0013] In an exemplary embodiment of one aspect of the present invention, adding the graphite, concentrated sulfuric acid and expansion agent into the reaction container may include: first adding graphite or concentrated sulfuric acid, and then adding the expansion agent while stirring; the stirring speed may be 300 to 1000 r / min, and the stirring time may be 2 to 20 min.
[0014] In an exemplary embodiment of one aspect of the present invention, the predetermined temperature may be 20 to 90° C., and the predetermined time may be 1 to 24 hours;
[0015] The obtained high expansion rate expanded graphite can be worm-shaped, and the expansion volume can be 100-550 mL / g.
[0016] In an exemplary embodiment of an aspect of the present invention, the stripping aid may be one or more of sodium percarbonate, ammonium bicarbonate and concentrated sulfuric acid;
[0017] The equipment used for the peeling treatment may include a high-speed mechanical stirrer, an ultrasonic disperser or a high-speed dispersing homogenizer;
[0018] The peeling treatment may be performed for 1 to 12 hours.
[0019] In an exemplary embodiment of one aspect of the present invention, the sedimentation separation can be carried out in a centrifuge, the centrifugal speed can be 3000-8000 rpm, the centrifugal time can be 3-10 min, and the solid content of the refined large-diameter graphene dispersion can be 55-85%.
[0020] In an exemplary embodiment of one aspect of the present invention, the graphene sheet diameter may be 5 to 25 μm, and the content of graphene with a sheet diameter greater than 10 μm in the total graphene may be greater than 70%, and the conductivity of the graphene may be 3.42×10 2 ~1.25×10 5 S / m, the graphene yield can be 50-90%.
[0021] In an exemplary embodiment of an aspect of the present invention, the number of graphene layers may be 1 to 10, wherein the content of the few-layer graphene may be more than 75%.
[0022] In an exemplary embodiment of one aspect of the present invention, the graphite raw material may be a flake powder of 50 to 100 meshes, and the carbon content in the graphite may be more than 85%;
[0023] The expansion agent may be one or more of sodium percarbonate and ammonium bicarbonate.
[0024] Another aspect of the present invention provides a graphene with a large flake diameter and high conductivity, wherein the graphene is prepared by any one of the preparation methods described above.
[0025] In an exemplary embodiment of another aspect of the present invention, the graphene sheet diameter may be 5 to 25 μm, and the content of graphene with a sheet diameter greater than 10 μm in the total graphene may be greater than 70%, and the conductivity of the graphene may be 3.42×10 2 ~1.25×10 5 S / m.
[0026] Compared with the prior art, the beneficial effects of the present invention may include at least one of the following:
[0027] (1) The preparation process of expandable graphite without oxidation intercalation, high temperature expansion process and corresponding process links can directly achieve one-time expansion to obtain expanded graphite, with good expansion effect and easy peeling;
[0028] (2) The graphene preparation process is simple, the production energy consumption is low, the reaction process is mild, no harmful gases are generated, and the process conditions are easy to control;
[0029] (3) Sodium percarbonate as an expansion and exfoliation aid can produce a large amount of gas to cause graphite to expand and exfoliate without causing oxidation to the graphite, thereby reducing the degree of structural damage and improving the expansion and exfoliation effect;
[0030] (4) The obtained graphene material has lower structural damage, fewer defects, more perfect structure, larger sheet diameter, better electrical properties, and is easier to promote and apply;
[0031] (5) The conductivity of graphene prepared by conventional redox method is usually 5.2×10 -2 ~12.6S / m, which is significantly lower than the conductivity of graphene prepared by the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 is the Raman spectrum of raw graphite;
[0033] Figure 2 The scanning electron microscope image of the raw graphite;
[0034] Figure 3 This is the Raman spectrum of graphene prepared in Example 1;
[0035] Figure 4 This is a scanning electron microscope image of the graphene prepared in Example 1;
[0036] Figure 5 This is the Raman spectrum of graphene prepared in Example 2;
[0037] Figure 6 This is a scanning electron microscope image of the expanded graphite prepared in Example 2;
[0038] Figure 7 This is a scanning electron microscope image of the graphene prepared in Example 2;
[0039] Figure 8 This is the Raman spectrum of graphene prepared in Example 3;
[0040] Fig. 9 This is a scanning electron microscope image of the graphene prepared in Example 3. DETAILED DESCRIPTION
[0041] Hereinafter, the graphene with large flake diameter and high conductivity and the preparation method thereof of the present invention will be described in detail with reference to the accompanying drawings and exemplary embodiments.
[0042] In a first exemplary embodiment of the present invention, a method for preparing graphene having a large sheet diameter and high conductivity comprises the steps of:
[0043] Step 1: Add graphite, concentrated sulfuric acid and expander into a reaction vessel at a ratio of 1:3-12:10-30 g / ml / g, and stir and mix to obtain a fluffy graphite mixture containing concentrated sulfuric acid and expander. Here, the reaction vessel can be an acid-resistant reactor with a high-speed mechanical stirring and heating device and a high-speed dispersing homogenizer attachment. g / ml / g means that the unit of graphite is g, the unit of concentrated sulfuric acid is ml, and the unit of expander is g.
[0044] Step 2: statically expand the fluffy graphite mixture obtained in the first step at a predetermined temperature for a predetermined time to obtain a crude high expansion rate expanded graphite. Here, the static expansion temperature can be 20 to 90°C, for example, 25°C, 40°C, 50°C, 60°C, 80°C. The static expansion time can be 1 to 24h, for example, 2h, 4h, 8h, 12h, 14h, 18h, 20h. Specifically, take a certain amount of expander, add it slowly and repeatedly in small amounts to the mixture of flake graphite and concentrated sulfuric acid (i.e., the fluffy graphite mixture in the first step), and stir continuously during the addition process. After mixing evenly, control the system to stand for a period of time under certain temperature conditions to directly obtain a crude high expansion rate expanded graphite. Among them, the mass ratio of graphite to expander can be 1:3 to 12, for example, 1:5, 1:8, 1:10, 1:11. Among them, the expander can be one or more of sodium percarbonate and ammonium bicarbonate. For example, the expander is sodium percarbonate.
[0045] Step 3: Add a stripping aid to the crude high expansion rate expanded graphite prepared in the second step, perform stripping treatment, and obtain a crude large-diameter graphene suspension. Here, the temperature during the stripping treatment can be 20 to 90°C, for example, 45°C. If the reaction temperature is too high, the stripping may not be thorough and damage the graphene structure. The stripping time can be 1 to 12 hours, for example, 4 hours. Here, the stripping aid can be one or more of sodium percarbonate, ammonium bicarbonate and concentrated sulfuric acid. For example, the stripping agent is sodium percarbonate and concentrated sulfuric acid, and the addition ratio of sodium percarbonate to graphite and expansion agent is 1:0.5 to 1g / g, and the ratio of concentrated sulfuric acid added in the third step to concentrated sulfuric acid added in the first step is 1:2 to 5ml / ml. The equipment used for the stripping treatment may include a high-speed mechanical stirrer, an ultrasonic disperser or a high-speed dispersing homogenizer, and the stripping treatment time can be 1 to 12 hours.
[0046] Step 4: Sediment the crude large-diameter graphene suspension to obtain a refined large-diameter graphene dispersion. The obtained crude large-diameter graphene suspension is placed in a centrifuge for sedimentation separation. The centrifugal speed is 3000-8000 rpm, such as 5000 rpm, the centrifugal time is 3-10 min, such as 5 min, and the solid content of the obtained refined large-diameter graphene dispersion is 55-85%, such as 70%.
[0047] Step 5: Filter, wash and dry the large-diameter refined graphene dispersion to obtain large-diameter high-conductivity graphene. Filter, wash and dry the obtained refined large-diameter graphene suspension to obtain large-diameter high-conductivity graphene. The graphene suspension should be washed to near neutrality, the generated waste liquid should be discharged after being neutralized by lime raw materials, and the precipitate should be used as a raw material for building materials; freeze drying for 48 hours to obtain large-diameter high-conductivity graphene powder.
[0048] In this exemplary embodiment, adding the graphite, concentrated sulfuric acid and expander into the reaction vessel may include: first adding graphite or concentrated sulfuric acid, and then adding the expander while stirring; the stirring speed may be 300 to 1000 r / min, for example, 500 r / min, 700 r / min, 900 r / min. The stirring time may be 2 to 20 min. Here, the purpose of mixing graphite with concentrated sulfuric acid is, on the one hand, to provide an acidic environment for the subsequent expansion process, react with the expander, and promote the expansion process. On the other hand, the graphite is acidified and the edges of the graphite are intercalated, making the graphite interlayers easier to open.
[0049] Furthermore, the obtained high expansion rate expanded graphite may be worm-shaped, and the expansion volume may be 100 to 550 mL / g.
[0050] In this exemplary embodiment, the sedimentation separation can be carried out in a centrifuge, the centrifugal speed can be 3000-8000 rpm, the centrifugal time can be 3-10 min, and the solid content of the refined large-diameter graphene dispersion can be 55-85%.
[0051] In this exemplary embodiment, the graphene sheet diameter may be 5 to 25 μm, and the content of graphene with a sheet diameter greater than 10 μm in the total graphene may be greater than 70%, and the conductivity of the graphene may be 3.42×10 2 ~1.25×10 5 S / m, the graphene yield can be 50-90%.
[0052] In this exemplary embodiment, the number of graphene layers can be 1 to 10, wherein the content of few-layer graphene (number of layers ≤ 5 layers) can reach more than 75%. Here, the higher the content of few-layer graphene in the graphene product, the better the conductive properties, and the better the application prospect in the subsequent preparation of functional composite coatings.
[0053] In this exemplary embodiment, the graphite raw material can be a flake powder of 50-100 mesh, and the carbon content in the graphite can reach more than 85%. Here, the larger the diameter of the graphite flakes, the larger its expansion volume; the carbon content of the graphite will affect its expansion effect, and too much impurity will consume reagents during the reaction process, thereby reducing the expansion volume.
[0054] In the second exemplary embodiment of the present invention, the graphene having a large flake diameter and high conductivity can be prepared by the preparation method described in the first exemplary embodiment.
[0055] In this exemplary embodiment, the graphene sheet diameter may be 5 to 25 μm, and the content of graphene with a sheet diameter greater than 10 μm in the total graphene may be greater than 70%, and the conductivity of the graphene may be 3.42×10 2 ~1.25×10 5 S / m.
[0056] Figure 1 is the Raman spectrum of raw graphite; Figure 2 The scanning electron microscope image of the raw graphite; Figure 3 This is the Raman spectrum of graphene prepared in Example 1; Figure 4 This is a scanning electron microscope image of the graphene prepared in Example 1; Figure 5 This is the Raman spectrum of graphene prepared in Example 2; Figure 6 This is a scanning electron microscope image of the expanded graphite prepared in Example 2; Figure 7 This is a scanning electron microscope image of the graphene prepared in Example 2;
[0057] Figure 8 This is the Raman spectrum of graphene prepared in Example 3; Fig. 9 This is a scanning electron microscope image of the graphene prepared in Example 3. The abscissa in the Raman spectrum represents the Raman shift, that is, the wave number difference of the scattered light relative to the incident light, and the ordinate represents the photon count, that is, the intensity of the scattered light.
[0058] In order to better understand the present invention, the content of the present invention is further explained below in combination with specific examples 1, 2, and 3, but the content of the present invention is not limited to the following examples.
[0059] Example 1
[0060] (1) Take 4 mL of 98% concentrated sulfuric acid and pour it into an acid-resistant reactor equipped with a stirring and heating device. Weigh 0.2 g of 50-mesh graphite and add it into the reactor and stir evenly.
[0061] (2) Weigh 0.8 g of sodium percarbonate, slowly add it into a reaction kettle and stir it evenly, and let it stand at room temperature for 12 hours to obtain crude expanded graphite with a high expansion rate.
[0062] (3) After the expansion is completed, 20 mL of concentrated sulfuric acid and 2 g of sodium percarbonate are added to the reactor, mixed evenly, and subjected to mechanical stirring and peeling reaction at room temperature for 4 h to obtain a crude large-diameter graphene suspension.
[0063] (4) placing the obtained crude large-scale graphene suspension in a centrifuge for sedimentation separation to obtain a refined large-scale graphene dispersion.
[0064] (5) After the reaction is completed, ultrapure water is used to wash the reaction product until it is neutral, and the product is filtered and freeze-dried for 48 hours to obtain large-diameter and highly conductive graphene powder.
[0065] Figure 1 is the Raman spectrum of raw graphite; Figure 2 The raw material graphite scanning electron microscope image (200X). Figure 1 and Figure 2 It can be seen that the raw graphite presents a dense layered structure and its surface is smooth. Figure 3 The Raman spectrum of the large-diameter and highly conductive graphene prepared in Example 1 is compared with Figure 1 and Figure 3 It can be seen that the D peak intensity in the Raman spectrum of graphene prepared in Example 1 is slightly enhanced compared with that of the raw graphite. Figure 4 This is a scanning electron microscope image (1.0KX) of graphene prepared in Example 1. Figure 2 Compared with the raw graphite, the graphite flakes are peeled off, the number of graphene layers obtained is small, and the number of graphene flakes with a diameter of 10 to 25 μm accounts for about 76%, and the conductivity is 5.27×10 4 S / m.
[0066] Example 2
[0067] (1)Same as Example 1.
[0068] (2) Weigh 1.6 g of sodium percarbonate, slowly add it into a reaction kettle and stir evenly, and place it in a constant temperature water bath at 85° C. for 2 h to obtain expanded graphite.
[0069] (3) After the expansion is completed, 20 mL of concentrated sulfuric acid and 2 g of sodium percarbonate are added to the reactor, mixed evenly, and stirred in a constant temperature water bath at 85° C. for 4 h to obtain a crude large-diameter graphene suspension.
[0070] (4) placing the obtained crude large-scale graphene suspension in a centrifuge for sedimentation separation to obtain a refined large-scale graphene dispersion.
[0071] (5) After the reaction is completed, ultrapure water is used to wash the reaction product until it is neutral, and the product is filtered and freeze-dried for 48 hours to obtain large-diameter and highly conductive graphene powder.
[0072] Figure 5 The Raman spectrum of the large-diameter and highly conductive graphene prepared in Example 2 is Figure 1 In comparison, the graphene structure produced is more complete and the degree of damage is lower. Figure 6The following is a scanning electron microscope image (100X) of the intermediate product expanded graphite prepared in Example 2. Figure 6 It can be seen that the expanded graphite is loose and worm-like, the graphite sheets are bent, irregular holes are formed at the edges, and the wrinkles on the sheet surface increase. This is because the decomposition of sodium percarbonate releases gas into the graphite interlayer, and the increased pressure of the gas generates thrust, which overcomes the interlayer van der Waals force and causes the graphite to expand rapidly along the c-axis direction. Figure 7 This is a scanning electron microscope image (2.0KX) of the large-diameter, highly conductive graphene prepared in Example 2. Figure 7 It can be seen that the obtained graphene samples have fewer wrinkles, a smooth surface, and a transparent gauze-like appearance. Some samples are stacked on each other, and the obtained sample sheets are thin and have few layers. This shows that the expanded graphite is completely exfoliated into graphene, proving that sodium percarbonate can effectively exfoliate expanded graphite in a strong acid environment. The number of graphene sheets obtained with a diameter of 10 to 25 μm accounts for about 80%, and the conductivity is 1.18×10 5 S / m.
[0073] Example 3
[0074] (1)Same as Example 1.
[0075] (2) Weigh 2.4 g of sodium percarbonate, slowly add it into a reaction kettle and stir it evenly, and let it stand at room temperature for 12 hours to obtain expanded graphite.
[0076] (3) After the expansion is completed, 20 mL of concentrated sulfuric acid and 2 g of sodium percarbonate are added to the reactor, mixed evenly, and stirred for exfoliation reaction at room temperature for 4 h to obtain a crude large-diameter graphene suspension.
[0077] (4) placing the obtained crude large-scale graphene suspension in a centrifuge for sedimentation separation to obtain a refined large-scale graphene dispersion.
[0078] (5) After the reaction is completed, ultrapure water is used to wash the reaction product until it is neutral, and the product is filtered and freeze-dried for 48 hours to obtain large-diameter and highly conductive graphene powder.
[0079] Figure 8 This is the Raman spectrum of the large-diameter, highly conductive graphene prepared in Example 3. Figure 8 It can be seen that the degree of graphene structure damage is low. Fig. 9 The scanning electron microscope image (2.0KX) of the large-diameter and highly conductive graphene prepared in Example 3 is shown in Figure 2. Figure 7 Compared with the graphene sheets obtained by the method of quartz crystallization, the thickness and diameter of the obtained graphene sheets are different. This is because the different expansion degrees in the early stage will lead to different peeling effects. It can be seen that the larger the expansion volume of the precursor expanded graphite, the thinner the graphene sheets obtained by peeling and the larger the diameter of the sheets. The number of graphene sheets with a diameter of 10 to 25 μm accounts for about 83%, and the conductivity is 6.59×104 S / m.
[0080] In summary, the beneficial effects of the present invention may include at least one of the following:
[0081] (1) The preparation process of expandable graphite without oxidation intercalation, high temperature expansion process and corresponding process links can directly achieve one-time expansion to obtain expanded graphite, with good expansion effect and easy peeling;
[0082] (2) The graphene preparation process is simple, the production energy consumption is low, the reaction process is mild, no harmful gases are generated, and the process conditions are easy to control;
[0083] (3) Sodium percarbonate as an expansion and exfoliation aid can produce a large amount of gas to cause graphite to expand and exfoliate without causing oxidation to the graphite, thereby reducing the degree of structural damage and improving the expansion and exfoliation effect;
[0084] (4) The obtained graphene material has lower structural damage, fewer defects, more perfect structure, larger sheet diameter, better electrical properties, and is easier to promote and apply;
[0085] (5) The conductivity of graphene prepared by conventional redox method is usually 5.2×10 -2 ~12.6S / m, which is significantly lower than the conductivity of graphene prepared by the present invention.
[0086] Although the present invention has been described above with reference to the accompanying drawings and exemplary embodiments, it should be apparent to those skilled in the art that various modifications may be made to the above embodiments without departing from the spirit and scope of the claims.
Claims
1. A method for preparing graphene with large sheet diameter and high conductivity, characterized in that: The preparation method comprises the steps of: Add graphite, concentrated sulfuric acid and an expander into a reaction container at a ratio of 1:3-12:10-30 g / ml / g, and stir and mix evenly to obtain a fluffy graphite mixture containing concentrated sulfuric acid and an expander; The expansion agent is one or more of sodium percarbonate and ammonium bicarbonate; wherein sodium percarbonate is used as an expansion and exfoliation aid to generate gas to expand and exfoliate the graphite without causing oxidation to the graphite; statically expand the fluffy graphite mixture at a predetermined temperature for a predetermined time to obtain crude high expansion rate expanded graphite; Adding a stripping aid to the crude high expansion rate expanded graphite to perform a stripping treatment to obtain a crude large-diameter graphene suspension; The stripping aid is one or more of sodium percarbonate, ammonium bicarbonate and concentrated sulfuric acid; Sedimenting and separating the crude large-sheet graphene suspension to obtain a refined large-sheet graphene dispersion; The large-diameter purified graphene dispersion is filtered, washed, and dried to obtain large-diameter highly conductive graphene.
2. The method for preparing graphene with large sheet diameter and high conductivity according to claim 1, characterized in that: The graphite, concentrated sulfuric acid and expansion agent are added into the reaction container, which comprises: firstly adding graphite or concentrated sulfuric acid, and then adding the expansion agent while stirring; the stirring speed is 300-1000 r / min, and the stirring time is 2-20 min.
3. The method for preparing graphene with large sheet diameter and high conductivity according to claim 1, characterized in that: The predetermined temperature is 20 to 90° C., and the predetermined time is 1 to 24 hours; The obtained high expansion rate expanded graphite is worm-shaped, and the expansion volume is 100-550 mL / g.
4. The method for preparing graphene with large sheet diameter and high conductivity according to claim 1, characterized in that: The equipment used for the peeling treatment includes a high-speed mechanical stirrer, an ultrasonic disperser or a high-speed dispersing homogenizer; The temperature during the stripping treatment is 20 to 90° C., and the time of the stripping treatment is 1 to 12 hours.
5. The method for preparing graphene with large sheet diameter and high conductivity according to claim 1, characterized in that: The sedimentation separation is carried out in a centrifuge, the centrifugal speed is 3000-8000 rpm, the centrifugal time is 3-10 minutes, and the solid content of the refined large-diameter graphene dispersion is 55-85%.
6. The method for preparing graphene with large sheet diameter and high conductivity according to claim 1, characterized in that: The graphene sheet diameter is 5 to 25 μm, and the content of graphene with a sheet diameter greater than 10 μm in the total graphene is more than 70%, and the conductivity of the graphene is 3.42×10 2 ~1.25×10 5 S / m, graphene yield is 50-90%.
7. The method for preparing graphene with large sheet diameter and high conductivity according to claim 1 or 6, characterized in that: The number of layers of the graphene is 1 to 10, wherein the content of the few-layer graphene is more than 75%.
8. The method for preparing graphene with large sheet diameter and high conductivity according to claim 1, characterized in that: The graphite raw material is a flake powder with a mesh size of 50 to 100, and the carbon content in the graphite is more than 85%.
9. A graphene having a large sheet diameter and high conductivity, characterized in that: The graphene is prepared by the preparation method according to any one of claims 1 to 8.
10. The graphene with large flake diameter and high conductivity according to claim 9, characterized in that: The graphene sheet diameter is 5 to 25 μm, and the content of graphene with a sheet diameter greater than 10 μm in the total graphene is more than 70%, and the conductivity of the graphene is 3.42×10 2 ~1.25×10 5 S / m.
Citation Information
Patent Citations
Method for preparing large-size high-quality graphene with controllable number of layers
CN104058396A
Rapid expanded graphite preparation method and wet peeling method for preparing graphene
CN109824040A
Copper-based modified graphene oxide composite material with high thermal conductivity and preparation method thereof
CN110468441A